Language in the brain - Schnelle, Helmut (Cambridge, [England] Cambridge University Press, 2010)
"Linguistics, neurocognition, and phenomenological psychology are fundamentally different fields of research. Helmut Schnelle provides an interdisciplinary understanding of a new integrated field in which linguists can be competent in neurocognition and neuroscientists in structure linguistics. Consequently the first part of the book is a systematic introduction to the function of the form and meaning-organising brain component - with the essential core elements being perceptions, actions, attention, emotion and feeling. Their descriptions provide foundations for experiences based on semantics and pragmatics. The second part is addressed to non-linguists and presents the structural foundations of currently established linguistic frameworks. This book should be serious reading for anyone interested in a comprehensive understanding of language, in which evolution, functional organisation and hierarchies are explained by reference to brain architecture and dynamics"--Provided by publisher.
Machine generated contents note: Part I. Introducing Cognitive Neuroscience to Linguists: 1. The brain in functional perspective; 2. Organization in complex organisms; 3. Neural perspectives of semantics: examples of seeing, acting, memorizing, meaningful understanding, feeling, and thought; 4. Combination and integration of intelligent thought and feeling; Part II. Introducing Linguistics to Scientists: 5. Introducing formal grammar; 6. Grammar as life; 7. Integrating language organization in mind and brain - the world of thinking and knowing, liking or hating other people's mind/brain/bodies; 8. Dynamic language organization in stages of complexity.
Keywords: Neurolinguistics; Cognitive neuroscience